Shifting paradigms: a pivotal study on laparoscopic resection for colovesical fistulas in diverticular disease - Rizzuto, Antonia; Andreuccetti, Jacopo; Bracale, Umberto; Silvestri, Vania; Pontecorvi, Emanuele; Reggio, Stefano; Sagnelli, Carlo; Peltrini, Roberto; Amaddeo, Angela; Bozzarello, Cristina; Pignata, Giusto; Cuccurullo, Diego; et al. (Frontiers in Surgery, 2024)
Colovesical fistulas (CVFs) pose a challenge in diverticulitis, affecting 4% to 20% of sigmoid colon cases. Complicated diverticular disease contributes significantly, accounting for 60-70% of all CVFs. Existing studies on laparoscopic CVF management lack clarity on its effectiveness in diverticular cases compared to open surgery. This study redefines paradigms by assessing the potentiality, adequacy, and utility of laparoscopy in treating CVFs due to complicated diverticular disease, marking a paradigm shift in surgical approaches.Ospedale Monaldi A.O.R.N dei Colli and University Federico II, Naples, Italy, patients undergoing surgery for CVF secondary to diverticular disease between 2010 and 2020 were examined. Comprehensive data, including demographics, clinical parameters, preoperative diagnoses, operative and postoperative details, and histopathological examination, were meticulously recorded. Patients were classified into open surgery (Group A) and laparoscopy (Group B). Statistical analysis used IBM SPSS Statistic 19.0.From January 2010 to December 2020, 76 patients underwent surgery for colovesical fistula secondary to diverticular disease. Laparoscopic surgery (Group B, n=40) and open surgery (Group A, n=36) showed no statistically significant differences in operative time, bladder suture, or associated procedures. Laparoscopy demonstrated advantages, including lower intraoperative blood loss, reduced postoperative primary ileus, and a significantly shorter length of stay. Postoperative morbidity differed significantly between groups. Mortality occurred in Group A but was unrelated to surgical complications. No reoperations were observed. Two-year follow-up revealed no fistula recurrence.This pivotal study marks a paradigm shift by emphasizing laparoscopic resection and primary anastomosis as a safe and feasible option for managing CVF secondary to diverticular disease. Comparable conversion, morbidity, and mortality rates to the open approach underscore the transformative potential of these findings. The study's emphasis on patient selection and surgeon experience challenges existing paradigms, offering a progressive shift toward minimally invasive solutions.